1971
DOI: 10.1073/pnas.68.2.367
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Methionine Biosynthesis in Escherichia coli: Mapping of the metJ Locus and Properties of a metJ + / metJ - Diploid

Abstract: MetJ-mutants of Escherichia coli have elevated nonrepressible levels of the enzymes of methionine biosynthesis and S-adenosylmethionine synthetase (ATP :L-methionine S-adenosyltransferase, EC 2.5.1.6). In E. coli, as in Salmonella typhimurium, the metJ locus is close to metB (95% cotransduction of metB and metJ markers), but in E. coli the order is reversed, with metJ mapping clockwise to metB. A stable merodiploid, heterozygous for metJ, is subject to repression by methionine. Thus, metJ functions via a diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 14 publications
(5 reference statements)
3
27
0
Order By: Relevance
“…the relative sensitivity of met gene promoters to induction under SAM-limiting conditions (Table 4; Greene et al, 1973;Holloway et al, 1970); and in our metJ : : Tn5 (no aporepressor) and metK : : Tn5 (limited SAM synthesis) cells (Table 5; Greene et al, 1973;Su & Greene, 1971). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the relative sensitivity of met gene promoters to induction under SAM-limiting conditions (Table 4; Greene et al, 1973;Holloway et al, 1970); and in our metJ : : Tn5 (no aporepressor) and metK : : Tn5 (limited SAM synthesis) cells (Table 5; Greene et al, 1973;Su & Greene, 1971). …”
Section: Discussionmentioning
confidence: 99%
“…Mutants of the more common type have decreased in vivo pools of SAM as a result of impaired SAM synthetase activity, and the defects map to metK (Greene et al, 1973;Hafner et al, 1977). Mutations of the second class map to metJ, and genetic and biochemical evidence identified the corresponding small protein as a DNAbinding aporepressor of met gene transcription (Su & Greene, 1971). These results suggested that a complex of MetJ and SAM binds a common nucleotide sequence in the promoters of target genes to prevent their transcription (Greene et al, , 1973Hobson & Smith, 1973).…”
Section: Introductionmentioning
confidence: 95%
“…Assuming that S-adenosylmethionine (SAM) is the co-repressor, Chater felt that the available evidence was in favour of metK rather than metJ coding for SAM synthetase, and recently Hobson (personal communication) has shown that SAM synthetase levels in some metK mutants vary from o to 25 % of those in wild-type or metJ mutants. Certainly the derepressed state of methionine enzymes in mutants of Escherichia coli K 1 2 with low levels of SAM synthetase and in others constitutive for the same enzyme (and apparently analogous to the Salmonella typhimurium metJ mutants -Holloway, Greene & Su, 1970; Su & Greene, 1971), also clearly implicate SAM in repression control of methionine synthesis in E. coli. However, the existence of SAM synthetase-deficient mutants implies that this enzyme may be dispensable which seems unlikely because of the direct involvement of SAM in critical intracellular methylation processes.…”
Section: Discussionmentioning
confidence: 99%
“…This protein interacts with S-adenosylmethionine to form an active complex that presumably functions as a classical repressor (13,17). The metJ gene of S. typhimurium has been cloned and its nucleotide sequence has been determined (18,19).…”
mentioning
confidence: 99%
“…Promoter Pjl was negatively regulated by the metJ gene product and by methionine. Although PJ2 regulation remained unclear, evidence is presented which suggests that it is not negatively regulated like pJl.In both Salmonella typhimurium and Escherichia coli the metJ gene codes for a protein that is involved in the regulation of the methionine pathway (5,13,17). This protein interacts with S-adenosylmethionine to form an active complex that presumably functions as a classical repressor (13,17).…”
mentioning
confidence: 99%